RESULTS OF RETROSPECTIVE OBSERVATIONAL STUDY OF ADALIMUMAB SAFETY AND EFFICACY IN PATIENTS WITH JUVENILE ARTHRITIS AND UVEITIS - Е.I. Alexeeva; Е.V. Mitenko; Т.М. Bzarova; S.I. Valieva; А.М. Chomakhidze; K.B. Isaeva; Е.G. Chistyakova; R.V. Denisova; T.V. Sleptsova; Т.Yu. Polyaeva; А.N. Fetisova ("Paediatrician" Publishers LLC, 2011)
The article contains results of retrospective observational study of adalimumab safety and efficacy in 67 juvenile arthritis and juvenile arthritis with eye involvement patients refractory to classical immunosuppressive treatment. It also contains a description of a recombinant biological medication - adalimumab: already on the 4th week of treatment acute inflammatory changes in the affected joints were relieved, joint motion range fully recovered; by the week 8 - full remission of the uveitis was reported in 45% of affected eyes (27/61), normalized disease activity lab parameters such as ESR, serum C-reactive protein.Key words: children, juvenile rheumatoid arthritis, rheumatoid uveitis, adalimumab. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 96-102)